2016
DOI: 10.1371/journal.pone.0148547
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 Replication and Expression in Differentiating Erythroid Progenitor Cells

Abstract: The pathogenic Parvovirus B19 (B19V) is characterized by a strict adaptation to erythroid progenitor cells (EPCs), a heterogeneous population of differentiating cells with diverse phenotypic and functional properties. In our work, we studied the dynamics of B19V infection in EPCs in dependence on the cell differentiation stage, in terms of distribution of infected cells, synthesis of viral nucleic acids and production of infectious virus. EPCs at early differentiation stage led to an abortive infection, withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 65 publications
1
52
0
Order By: Relevance
“…In order to define the correlation of the VP1u receptor expression with the cellular permissivity for B19V infection, we expanded CD34+ hematopoietic stem cells ex vivo towards the erythroid lineage [4,5,6,16] and tested the MS2-VP1u internalization, virus uptake and infection along the differentiation. The results show that MS2-VP1u internalization (Figure 4A), B19V uptake (Figure 4C) and virus infection (Figure 4D) all show a similar profile along the erythroid development.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to define the correlation of the VP1u receptor expression with the cellular permissivity for B19V infection, we expanded CD34+ hematopoietic stem cells ex vivo towards the erythroid lineage [4,5,6,16] and tested the MS2-VP1u internalization, virus uptake and infection along the differentiation. The results show that MS2-VP1u internalization (Figure 4A), B19V uptake (Figure 4C) and virus infection (Figure 4D) all show a similar profile along the erythroid development.…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that this extreme tropism is determined by intracellular permissivity factors as well as by a specific internalization into this cell type [4,5,7]. Previous studies have shown that only erythroid cells around the proerythroblast stage support efficient viral replication and production of infectious progeny [3,4,5,6]. To avoid predominant and abortive infections into non-permissive cells, B19V needs to restrict the virus uptake to permissive erythroid differentiation stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not all erythropoietic cells are equally permissive for viral replication (Bua et al, 2016; Takahashi et al, 1990). B19V infects EPCs by binding P antigen (glycosphingolipid globoside), the primary B19V receptor (Brown et al, 1993).…”
Section: Introductionmentioning
confidence: 99%